2019
DOI: 10.1038/s41598-019-39294-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduced habit-driven errors in Parkinson’s Disease

Abstract: Parkinson’s Disease can be understood as a disorder of motor habits. A prediction of this theory is that early stage Parkinson’s patients will display fewer errors caused by interference from previously over-learned behaviours. We test this prediction in the domain of skilled typing, where actions are easy to record and errors easy to identify. We describe a method for categorizing errors as simple motor errors or habit-driven errors. We test Spanish and English participants with and without Parkinson’s, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…One notable instance is the differential loss of dopamine neurotransmission from this region in Parkinson’s disease 7 a putative pathophysiological condition linked to the cost of life-long use of habits 105 . The problems Parkinson’s disease patients have with walking and writing 8, 106, 107 and the new learning of experimental habits 108, 109 , have been interpreted as an inability to express stimulus-response habits. In contrast, other neuropsychiatric complications such as addictions exhibit an excessive cue-dependent use of certain rewards linked to increased posterior putamen activity 10, 110 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One notable instance is the differential loss of dopamine neurotransmission from this region in Parkinson’s disease 7 a putative pathophysiological condition linked to the cost of life-long use of habits 105 . The problems Parkinson’s disease patients have with walking and writing 8, 106, 107 and the new learning of experimental habits 108, 109 , have been interpreted as an inability to express stimulus-response habits. In contrast, other neuropsychiatric complications such as addictions exhibit an excessive cue-dependent use of certain rewards linked to increased posterior putamen activity 10, 110 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is of great interest to understand how automatic habitual control operates in the normal circumstances of everyday life. It is also important to understand how brain disorders such as Parkinson’s disease 7, 8 , obsessive-compulsive disorder 9 , and drug addictions 10 lead to clinically dysfunctional patterns of habitual use of behaviour. Despite the importance of habitual control in daily life and clinical pathology, formal investigation of the inherent stimulus-response associations established in everyday life is in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…In PD, depletion of dopamine in the basal ganglia causes the complex motor deficit of bradykinesia-reduced speed, reduced amplitude, loss of rhythm and loss of ability to sustain repetitive movement. Habitual actions such as speech and gait, which are associated with higher degrees of automaticity, are particularly affected [72,73]. It has been shown that over 80% of PD patients suffer from dysarthria [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…Summary statistics are found in table 1. Bannard et al 2019). Patients were recruited to be in the early stages of PD (Hoehn-Yahr stages 0 − 2.5, UPDRS < 20 in the medicated state), with normal cognitive function and < 5 years from a confirmed diagnosis.…”
Section: Datasetsmentioning
confidence: 99%
“…Eleven patients and nine age-matched controls were tested during a visit to a hospital clinic in Spain (see Bannard et al 2019). The inclusion criteria for patients was the same as for the clinictested English sample.…”
Section: In-clinic Spanish Copy-typingmentioning
confidence: 99%